Formula of Investment Success: Comparative Analysis of Legislation for Investment Activities Development - MURZAGALIYEVA, Assel M. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Investments are an integral part of the modern economy, as they contribute to making a profit and achieving a positive effect. Therefore, the author chose this topic for study. The main purpose of the work is to determine the investment success, using the example of development of investment activities of the United States and Japan. The author found that 74% of all direct foreign investment of the United States is investment in developed countries, where you can get a good profit. First of all, American business invests in the Netherlands, Britain, Luxembourg, Canada, Ireland. Having studied the issue of investment success, the author derived a formula that promotes development. It includes liberal legislation, a government collegial body, additional mechanisms, free economic zones, access to the global market and internal potential. These components contribute to the development of investment activities.